Corrosion of pure magnesium and a WE43 magnesium alloy studied by advanced acoustic emission analysis. (December 2018) - Knapek, Michal; Minárik, Peter; Čapek, Jan; Král, Robert; Kubásek, Jiří; Chmelík, František
Abstract: The corrosion behaviour of magnesium and a WE43 magnesium alloy in a 1 M NaCl aqueous solution was studied by potentiodynamic polarisation and advanced acoustic emission (AE) analyses. The AE parameters suitable for monitoring the corrosion in magnesium were shown to be the AE counts, rise time, and duration. Moreover, the mechanisms of corrosion in these materials, i.e., ion exchange, rupture of the protective film, and pitting corrosion were identified and their evolution was followed by the novel Adaptive sequential k-means clustering technique. The presented methods can also be suitable for monitoring different materials and for industrial applications.